Examining child schooling/care location and child temperament as predictors of restaurant-related behaviors during the COVID-19 pandemic: findings from a nationally representative survey - Goldsmith, Juliana; Ferrante, Mackenzie J.; Tauriello, Sara; Epstein, Leonard H.; Leone, Lucia A.; Anzman-Frasca, Stephanie (Frontiers in Nutrition, 2024)
Purpose Emerging research highlights impacts of the COVID-19 pandemic on U.S. families, including changes in eating behavior and increased child body mass index. Aims of the present study were to examine whether child temperament and at-home vs. out-of-home childcare/school predicted families’ restaurant-related behaviors during the pandemic. Examining energy balance-related behaviors, like restaurant patronage, during the pandemic can help better understand lasting impacts on child health behaviors and health outcomes. Methods An online survey was administered to U.S. parents with a 4-to-8-year-old child in October 2020 (n = 1,000). Linear and logistic regression examined whether child temperament and at home vs. out-of-home childcare/school predicted: (1) the frequency the child consumed restaurant meals (take-out, delivery, dine-in), (2) who chose the child’s restaurant meal, and (3) parent-reported reasons for the child’s meal choice. Income, education, employment, race/ethnicity, and regional COVID-19 restrictions were tested as covariates. Results Parents with children higher on negative affectivity reported more frequent restaurant use in-person (p < 0.05) and via delivery (p < 0.05) compared to parents of children lower on negativity. Child negativity was also linked with parent-reported reasons for children’s restaurant meal choices. Parents of children receiving at-home childcare/schooling used delivery services less frequently than those receiving out-of-home care or schooling (p < 0.01). Conclusion These findings suggest that individual and family factors may impact restaurant use and the meal selection process for children using restaurants during and beyond the COVID-19 era. Continued examination of individual differences in the impacts of the COVID-19 pandemic can facilitate intervention and policy approaches that fit with different families’ needs.